2015
DOI: 10.5194/acp-15-1807-2015
|View full text |Cite
|
Sign up to set email alerts
|

Experimentally measured morphology of biomass burning aerosol and its impacts on CCN ability

Abstract: Abstract. This study examines the morphological properties of freshly emitted and atmospherically aged aerosols from biomass burning. The impacts of particle morphology assumptions on hygroscopic predictions are examined. Chamber experiments were conducted at the University of California, Riverside, Center for Environmental Research and Technology (CE-CERT) atmospheric processes lab using two biomass fuel sources: manzanita and chamise. Morphological data was obtained through the use of an aerosol particle mas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 59 publications
2
22
0
Order By: Relevance
“…The covering filled the void spaces in the agglomerate, which resulted in a higher effective density. The results are consistent with previous work on the photochemical exposure of both biomass burning aerosol and diesel exhaust (Nakao et al 2011, Giordano et al 2015 that showed particles become denser with photochemical aging. Like the volatility results, the rate of change of the bulk effective densities between the two fuels are similar for the first two hours of photochemical aging.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The covering filled the void spaces in the agglomerate, which resulted in a higher effective density. The results are consistent with previous work on the photochemical exposure of both biomass burning aerosol and diesel exhaust (Nakao et al 2011, Giordano et al 2015 that showed particles become denser with photochemical aging. Like the volatility results, the rate of change of the bulk effective densities between the two fuels are similar for the first two hours of photochemical aging.…”
Section: Resultssupporting
confidence: 92%
“…Here, the fractal-like dimension is a measure of the deviation from sphericity of the particle where D f ′<3 indicates a non-spherical particle. Additional information on the fractal nature of biomass burning particles is reported in Giordano et al (2015).…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noted that the vehicle exhaust emissions may be fractal, which can affect the electrical mobility diameter measurements and subsequent CCN activation. 27,28 However, for the analysis of these emissions, the particles are assumed to be spherical. It is assumed that emissions during nonregeneration are likely organic and fractal and will lower κ measured values.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…We stress that the call for consistency between measurement and RTM calculations is by no means a call for abandoning the investigation of the morphology of carbonaceous particles. This study focuses on the climate effect of OA light absorption, and the conclusions do not necessarily apply to other climate‐relevant properties (e.g., cloud condensation nuclei activation) [ Giordano et al ., ]. Furthermore, understanding the evolution of morphology upon atmospheric aging is of major importance.…”
Section: Discussionmentioning
confidence: 99%